A Late Roman 'Hall' at Batten Hanger, West Sussex. (29th January 2016) - Kenny, James; Lyne, Malcolm; Magilton, John; Buckland, Paul
Abstract: Excavation of the latest surviving structures of the villa at Batten Hanger in West Sussex indicates that a large aisled building was demolished in the late fourth or fifth century and replaced by a large hall 31.6 m long by 11.5 m wide, orientated approximately east–west. The survival of pad stones shows this space to have been divided into seven bays, with the more westerly bays screened off by a cross wall. The east wall of the building had collapsed outwards and was largely complete. A coin of Valentinian III suggests that occupation continued at least to the middle of the fifth century. The Supplementary Material available online (http://journals.cambridge.org/bri ) contains a detailed presentation of the coin hoard and the pottery assemblages.